Theoretical Study on the Site and Regularity of Chiral Ru(II) Polypyridyl Complexes Binding to Mismatched DNA-Base-Pair - Yan Liao, Si; Liang Lu, Hai; Fang Miao, Ti; Cheng Zheng, Kang (Asian Journal of Chemistry, 2013)
In order to perform theoretical studies on the interactions between Ru(II) complexes and DNA, a combined methodology of molecular mechanics (MM+), quantum chemistry (DFT) and molecular docking was applied to establish the valuable model and hereby to study the interaction of Ru(II) complexes with mismatched DNA containing sheared G×A base pairs. The groove selectivity, base pair recognition, binding energy at different base pair site and binding configuration were investigated, using well-known DNA intercalator [Ru(phen)2(dppz)]2+ as a molecular probe. On the basis of these testing researches, a series of chiral Ru(II) complexes D, L-[Ru(bpy)2L]2+ [L = o-hpip, m-hpip, p-hpip] {hpip = 2-(hydroxyphenyl)imidazo[4,5-f][1,10-phenanthroline]} were selected to carry out a significant study on their DNA-groove selectivity, DNA-binding energy and binding configuration at the specific base-pair site which has been specially recognized by [Ru(phen)2(dppz)]2+ molecular probe. The effects of chirality, different position of substitute group and intramolecular hydrogen bond of these studied complexes on the complex-DNA interaction were also discussed and the related regularities were well revealed. The obtained results help to understanding the control regulations and the action mechanism between the complex and DNA and further directing the design and synthesis of this kind of Ru(II) polypyridyl complex.